C-KIT Analysis and Targeted Molecular Sequencing of Mesonephric Carcinomas of the Female Genital Tract. (April 2020) - Pors, Jennifer; Ho, Julie; Prentice, Leah; Thompson, Emily; Cochrane, Dawn; Gibbard, Evan; Huntsman, David; Gilks, Blake; Hoang, Lynn N.
Abstract : Mesonephric carcinoma is a rare malignancy, thought to derive from Wolffian remnants. To date, no targeted molecular therapeutic options have been identified. On the basis of limited case reports, c-KIT immunohistochemical expression has been reported in female adnexal tumors of Wolffian origin, and targeted therapy with Imatinib has been attempted with mixed success. Currently, it is unclear whether c-KIT immunohistochemical expression is seen in mesonephric carcinoma, a tumor that is thought to be related to female adnexal tumors of Wolffian origin, and how this correlates with KIT mutational status. In this study, we assessed the immunohistochemical expression of c-KIT and KIT mutational status, in a series of 13 mesonephric neoplasms (5 cervical [including 2 cervical carcinosarcomas], 3 uterine corpora, 4 ovarian, and 1 vaginal/pelvic). The intensity of staining and proportion of cells showing cytoplasmic/membranous staining for c-KIT were recorded. KIT was sequenced using a next-generation sequencing panel that targeted 120 hotspots and 17 exons in 33 known actionable cancer genes. This panel included KIT exons 9, 11, and 13, and 6 hotspots (T670, D816, D820, N822, Y823, A829). Although c-KIT immunohistochemical expression was observed in the majority of mesonephric carcinomas (10/12 cases; 83%), no KIT mutations were detected. This cautions pathologists against the use of c-KIT immunohistochemistry as a surrogate marker for KIT -activating mutations in this setting. Consistent with previous studies, the majority of mesonephric neoplasms (10/13; 77%) harbored KRAS mutations. Additional mutations were found in CTNNB1 (2/13, 15%), TP53 (2/13, 15%), and PIK3CA (1/13, 8%).